Ecological niche shifts of understorey plants along a latitudinal gradient of temperate forests in north‐western Europe. Issue 10 (4th June 2013) - Wasof, Safaa; Lenoir, Jonathan; Gallet‐Moron, Emilie; Jamoneau, Aurélien; Brunet, Jörg; Cousins, Sara A. O.; De Frenne, Pieter; Diekmann, Martin; Hermy, Martin; Kolb, Annette; Liira, Jaan; Verheyen, Kris; et al.
Abstract Aim In response to environmental changes and to avoid extinction, species may either track suitable environmental conditions or adapt to the modified environment. However, whether and how species adapt to environmental changes remains unclear. By focusing on the realized niche (i.e. the actual space that a species inhabits and the resources it can access as a result of limiting biotic factors present in its habitat), we here examine shifts in the realized‐niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) of 26 common and widespread forest understorey plants across their distributional ranges. Location Temperate forests along a ca. 1800‐km‐long latitudinal gradient from northern France to central Sweden and Estonia. Methods We derived species' realized‐niche width from a β‐diversity metric, which increases if the focal species co‐occurs with more species. Based on the concept that species' scores in a detrended correspondence analysis (DCA) represent the locations of their realized‐niche positions, we developed a novel approach to run species‐specific DCAs allowing the focal species to shift its realized‐niche position along the studied latitudinal gradient while the realized‐niche positions of other species were held constant. Results None of the 26 species maintained both their realized‐niche width and position along the latitudinal gradient. Few species (9 of 26: 35%) shifted their realized‐niche width, but all shifted their realized‐niche position. With increasing latitude, most species (22 of 26: 85%) shifted their realized‐niche position for soil nutrients and pH towards nutrient‐poorer and more acidic soils. Main conclusions Forest understorey plants shifted their realized niche along the latitudinal gradient, suggesting local adaptation and/or plasticity. This macroecological pattern casts doubt on the idea that the realized niche is stable in space and time, which is a key assumption of species distribution models used to predict the future of biodiversity, hence raising concern about predicted extinction rates.